Intensity-Distance attenuation laws for the Portugal mainland using intensity data points - Le Goff, B. (2015)
In this study, new intensity-distance attenuation law is presented, using directly the intensity observations, rather than the subjective, and sometimes controversial, isoseismal lines. This intensity-distance attenuation law is the only one defined for Portugal mainland, which is expressed as a function of magnitude. We computed this attenuation law using the slope and the intercept of the logarithmic regression of 25 events, with magnitudes between 4.4 and 6.2. Using the Bakun and Wentworth method (1997), this new attenuation law allows performing better results in the earthquake epicentral position and magnitude estimations of the 1909 Benavente event than the Atkinston and Boore attenuation law (1997). This law also gives good results in the study of site effects, presenting good matches between intensity residuals and geological structures where site effects are expected.